2018
DOI: 10.1186/s13567-018-0607-x
|View full text |Cite
|
Sign up to set email alerts
|

Small ruminant lentivirus infection influences expression of acute phase proteins and cathelicidin genes in milk somatic cells and peripheral blood leukocytes of dairy goats

Abstract: The aim of the study was to analyze acute phase protein and cathelicidin gene responses to small ruminant lentivirus (SRLV) infection in goats. In uninfected goats, we found higher Cp and lower Fbγ mRNA levels in blood leucocytes (BL) than in milk somatic cells (MSC), as well as lower SAA, Hp, and CRP and higher Cp and AGP concentrations in blood serum than in milk. In SRLV-infected goats, we found higher Fbγ and MAP28 and lower Cp expression in MSC than in BL, and higher SAA, Hp, Fb, and MAP28 and lower AGP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
4
18
0
Order By: Relevance
“…It may also imply that during chronic mammary gland inflammation, when bacteria are present for a longer time in the whole udder, the tissues produce different molecules, such as APPs, to combat infection and reduce pathogenic propagation; however, these molecules are produced at a lower level than during acute inflammation to ensure that the host's cells are not permanently harmed. These findings are in line with different publications describing the immunological response of MECs during mammary gland inflammation [10,17,24,25], but the results for CLECs obtained in this study have not been described before.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It may also imply that during chronic mammary gland inflammation, when bacteria are present for a longer time in the whole udder, the tissues produce different molecules, such as APPs, to combat infection and reduce pathogenic propagation; however, these molecules are produced at a lower level than during acute inflammation to ensure that the host's cells are not permanently harmed. These findings are in line with different publications describing the immunological response of MECs during mammary gland inflammation [10,17,24,25], but the results for CLECs obtained in this study have not been described before.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, free hemoglobin is highly toxic to tissues due to the lipophilic character of heme (i.e., it interacts with the cellular lipid bilayer), and the iron present in heme facilitates the generation of reactive oxygen species [15]. Our research illustrates the extrahepatic nature of HP synthesis with MECs-a finding that is in line with other scientific reports [16][17][18].…”
Section: Discussionsupporting
confidence: 88%
“…They concluded that this difference was not due to the presence of the virus, but to inflammation. However, Reczyńska et al [ 65 ] did find an elevated level of SAA in the blood serum of SRLV-infected goats without clinical signs of CAE, as well as a simultaneous decrease of SAA and Cp levels in the milk of those animals. These results suggest that an analysis should be done in both types of biological material in parallel to diagnose CAE in animals without clinical symptoms of the disease.…”
Section: App Levels In Blood Serum Of Farm Dairy Ruminants During mentioning
confidence: 99%
“…All animals used in the experiment were healthy and in particular were free from small ruminant lentivirus (SRLV) infection, since it influences the expression levels of immune system genes (Bagnicka et al , 2018, Reczyńska et al , 2018). The animals were divided into two analogous groups (according to breed and parity) – the control and experimental – each containing six animals of two breeds: Polish White Improved (PWI) and Polish Fawn Improved (PFI).…”
Section: Methodsmentioning
confidence: 99%